A multicenter, prospective, advanced diagnostic bronchoscopy outcomes registry - Ernst, Armin; Simoff, Michael; Ost, David; Michaud, Gaetane; Chandra, Divay; Herth, Felix (Chest, 2010)
Background - Multiple new diagnostic bronchoscopic technologies are available, but little is known about their comparative performance and specific yield when adjusted for location of lesions, target size, and diagnosis. We present a multi-institutional prospective-outcomes database to assess diagnostic yields of advanced bronchoscopic procedures, as well as related morbidity and mortality. - Methods - Data were extracted and reviewed from an ongoing, paper-based, prospective, multi-institutional outcomes database for advanced diagnostic bronchoscopic procedures. All consecutive eligible patients are entered into this database, and information on demographics, procedure, and lesion characteristics as well as complications were documented. Descriptive statistical analyses were performed. - Results - A total of 310 diagnostic procedures were performed over a 1-year period in four institutions by 15 different clinicians. The majority of the patients were white (66%), male (56%), former smokers (55%), with a mean age of 61 ± 14 years. The average procedure time was 36 min, and the most common procedure was transbronchial needle aspiration (TBNA) (n = 198). Nodal tissue was obtained in 82.3% from TBNA sampling with a mean of three passes using endobronchial ultrasound guidance with a 22-gauge needle and mostly without on-site cytology. The overall diagnostic yield for all procedures was 75%. There were few complications, and none required a change in disposition. - Conclusions - Prospective and ongoing data analysis for bronchoscopic procedures is feasible and valuable. Lesion-adjusted diagnostic yields can be documented and potentially used for comparative assessment of different technologies and operators, as well as benchmarking and quality improvement initiatives. Extending the number of participating centers and web-based submission to minimize missing data components are the next, already-initiated steps.
Elektronische Reproduktion der Druck-Ausgabe
Available online 16 December 2015
Gesehen am 27.03.2023